2015
DOI: 10.1590/1982-0224-20140039
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytogenetic analyses of cryptic species within the Synbranchus marmoratus Bloch, 1795 (Synbranchiformes: Synbranchidae) grouping: species delimitations, karyotypic evolution and intraspecific diversification

Abstract: The fish species Synbranchus marmoratus has been reported to exist as a species complex due to high intraspecific karyotypic variability in spite of the difficulty or impossibility to distinguish them using morphological traits alone. The goal of this work was to use cytogenetic and molecular methods to determine the species delimitations and understand the karyoevolution of S. marmoratus using samples collected from distinct Brazilian localities. Among the analyzed specimens, a large degree of cytogenetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Other studies have reported that Hoplias malabaricus (Utsunomia et al 2014a), Synbranchus marmoratus (Torres et al 2005;Utsunomia et al 2014b), Rhamdia quelen (Martinez et al 2011), Sternopygus macrurus (de Almeida-Toledo et al 1993), Eigenmannia virescens (Silva et al 2009), E. trilineata (Moys es et al 2010) and Brachyhypopomus pinnicaudatus (Giora 2009) are species complexes, but this is the first time that Leporinus striatus and Pimelodus maculatus are listed as putative species complexes.…”
Section: Cryptic Speciesmentioning
confidence: 86%
“…Other studies have reported that Hoplias malabaricus (Utsunomia et al 2014a), Synbranchus marmoratus (Torres et al 2005;Utsunomia et al 2014b), Rhamdia quelen (Martinez et al 2011), Sternopygus macrurus (de Almeida-Toledo et al 1993), Eigenmannia virescens (Silva et al 2009), E. trilineata (Moys es et al 2010) and Brachyhypopomus pinnicaudatus (Giora 2009) are species complexes, but this is the first time that Leporinus striatus and Pimelodus maculatus are listed as putative species complexes.…”
Section: Cryptic Speciesmentioning
confidence: 86%
“…Once the majority of chromosomal rearrangements involve heterochromatic regions, especially in fish species [26, 27], this explains the centromeric rearrangements in M. albus . The co-localization of CMA 3 positive heterochromatin with the NOR loci also occurs in other synbranchids [25, 28], probably because of local changes in base composition (increase in GC content) due to the so-called GC-biased gene conversion that involves rDNA in many vertebrates, including ray-finned fishes [29].…”
Section: Discussionmentioning
confidence: 99%
“…They also form small populations, and although they prefer freshwater habitats, these fishes tolerate brackish and saline conditions [1]. On the other hand, as many individuals can be isolated in small lakes during dry years, the capacity of sex reversal observed in synbranchids could contribute to the viability of such populations, increasing the probability of the fixation of genetic differences and speciation processes [25, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the availability of refined cytogenetic methods have allowed identifying population polymorphism and unique evolutionary units, even within morphologically similar groups (Bitencourt et al, 2011;Utsunomia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%